Assessment of Proso millet Genotypes against Blast Caused by Pyricularia grisea (Cooke) Sacc. under Field Condition at Mid Hill Region of Nepal - Subedi, Subash; Neupane, Saraswati; Neupane, Prazwal; Shrestha, Jiban (Journal of Nepal Agricultural Research Council, 2022)
A total of 14 proso millet genotypes, including the farmers' variety, which was the most commonly cultivated landrace in the Karnali region and most susceptible to blast disease as a susceptible check, were evaluated for resistance to leaf blast at the Hill Crops Research Program, Kabre, Dolakha, Nepal during the summer seasons of 2020 and 2021. The experiment was conducted under natural epiphytotic conditions. The experiment revealed that none of the tested genotypes were found immune or highly resistant. Most of the genotypes showed moderately susceptible and susceptible reactions to the leaf blast disease for both experimental years. However, genotypes C04654, Humla-239, and C04651 were found to have lower blast severity and produce higher grain yields. Genotype C04654 was found as resistant with 34.6% disease severity and high yielding (2.6 t/ha), followed by Humla-239 and C04651 as moderately susceptible with 44.8 and 45.9% disease severity resulting grain yields of 2.5 and 2.4 t/ha, respectively. The higher disease severity (68.1%) with lower grain yield (1.4 t/ha) was recorded in the farmer's variety (susceptible check). The genotypes reported with lower blast severity and higher grain yield could be the source for the release of a leaf blast resistant and high-yielding proso millet variety in the mid-hill region of Nepal.